2009
DOI: 10.1007/s00270-009-9727-z
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Artery Embolization as a Primary Treatment for Benign Prostatic Hyperplasia: Preliminary Results in Two Patients

Abstract: Symptomatic benign prostatic hyperplasia (BPH) typically occurs in the sixth and seventh decades, and the most frequent obstructive urinary symptoms are hesitancy, decreased urinary stream, sensation of incomplete emptying, nocturia, frequency, and urgency. Various medications, specifically 5-α-reductase inhibitors and selective α-blockers, can decrease the severity of the symptoms secondary to BPH, but prostatectomy is still considered to be the traditional method of management. We report the preliminary resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
119
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(138 citation statements)
references
References 26 publications
6
119
0
13
Order By: Relevance
“…PAE is considered technically challenging and unilateral PAE has been reported in all of these preliminary studies [2][3][4]. In the present study, 15.6 % of patients underwent unilateral embolization due to significant atherosclerotic lesions and tortuosity of the iliac and prostatic arteries.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…PAE is considered technically challenging and unilateral PAE has been reported in all of these preliminary studies [2][3][4]. In the present study, 15.6 % of patients underwent unilateral embolization due to significant atherosclerotic lesions and tortuosity of the iliac and prostatic arteries.…”
Section: Discussionmentioning
confidence: 54%
“…Keywords Prostatic arterial embolization Á Unilateral Á Benign prostatic hyperplasia Á Lower urinary tract symptoms Preliminary studies have shown that prostatic arterial embolization (PAE) for the relief of lower urinary tract symptoms (LUTS) in patients with prostate enlargement/ benign prostatic hyperplasia (PE/BPH) is a promising, new, minimally invasive, image-guided therapy [1][2][3][4]. However, PAE is a technically challenging procedure with unilateral embolization and technical failure reported rates of approximately 10-15 and 7 %, respectively [1][2][3][4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The first report of this technique in the management of BPH in humans was by DeMeritt et al (14), who reported a single case of BPH with obstructive symptoms and blood loss refractory to other treatments that was successfully managed by PAE with 150 -250-m polyvinyl alcohol (PVA) particles. More recently there has been a report of two other patients in similar clinical scenarios treated with success with the use of 300 -500-m microspheres (15).…”
mentioning
confidence: 99%